Унифицированные модели элементов систем электроснабжения на основе уравнений в фазных координатах - Веприк, Ю.Н.; Небера, О.А. (Електротехніка і електромеханіка, 2015)
В статье рассматриваются методы математического моделирования элементов электрических систем, которые
основаны на составлении систем дифференциальных уравнений и их решении методами численного интегрирования.
Представлены дискретные уравнения электрических машин в системе координат d-q-0 и в системе фазных координат. Предложен алгоритм моделирования отдельных элементов электрических систем для разработки математической модели систем электроснабжения в переходных режимах. У статті розглядаються методи математичного моделювання елементів електричних систем, що засновані на
складанні систем диференціальних рівнянь та їх розв'язанні методами чисельного інтегрування. Представлені дискретні рівняння електричних машин в системі координат d-q-0 і в системі фазних координат. Запропоновано алгоритм моделювання окремих елементів електричних систем для розробки математичної моделі систем електропостачання в перехідних режимах. Purpose. The models of electrical machines in the phase coordinates, the universal algorithm for the simulation of separate
elements in a d-q coordinates system and in a phase-coordinates
system are proposed. Methodology. Computer methods of investigation of transients in electrical systems are based on a compilation of systems of differential equations and their numerical
integration solution methods. To solve differential equations an
implicit method of numerical integration was chosen. Because it
provides to complete structural simulation possibility: firstly
developing models of separate elements and then forming a
model of the complex system. For the mathematical simulation
of electromagnetic transients in the elements of the electrical
systems has been accepted the implicit Euler-Cauchy method,
because it provides a higher precision and stability of the computing processes. Results. In developing the model elements
identified two groups of elements: - Static elements and electrical machines in the d-q coordinates; - Rotating electrical machines in phase coordinates. As an example, the paper provides
a model of synchronous and asynchronous electric machines in
the d-q coordinates system and the phase coordinate system.
The generalization algorithm and the unified notation form of
equations of elements of an electrical system are obtained. It
provides the possibility of using structural methods to develop a
mathematical model of power systems under transient conditions. Practical value. In addition, the using of a computer
model allows to implement multivariant calculations for research and study of factors affecting the quantitative characteristics of the transients.